022 Leucine Rich Repeat Containing 8A Anion Channels Modulate Vascular Reactivity in the Pudendal Artery. (1st May 2022) - Choi, H.; Nguyen, H.; Priviero, F.; Webb, R.C.; Lamb, F.
ABSTRACT: Introduction: Erectile dysfunction (ED) is characterized by an inability to develop or maintain penile erection during sexual activity. The internal pudendal artery (IPA) is the primary supplier of genital blood flow. Reactive oxygen species (ROS) generation is necessary for intracellular signaling, but excessive ROS production can promote ED. NADPH oxidase (Nox) produces extracellular superoxide (O2 - ) in the vasculature and we have demonstrated that Leucine Rich Repeat Containing 8 (LRRC8) Volume Regulated Anion Channels (VRACs) physically associate with and regulate Nox1. LRRC8A downregulation or channel inhibition decreases extracellular O2 - production by Nox1 and dramatically reduces the inflammatory response to tumor necrosis factor alpha. Objective: We hypothesize that smooth muscle-specific LRRC8A knockout (KO) increases vascular relaxation in IPA. Methods: The IPAs from male wildtype (WT) and LRRC8A KO (smooth muscle-specific) mice were used in wire myograph studies. Results: Following phenylephrine (PE, 2x10 -6 M)-induced contraction, cumulative relaxation-response curves to acetylcholine (ACh, 10 -9 to 3x10 -6 M), sodium nitroprusside (SNP, 10 -9 to 10 -5 M), and a soluble guanylyl cyclase activator (BAY60-2770, 10 -9 to 10 -6 M) were measured. Endothelium-dependent relaxation to ACh was increased in LRRC8A KO compared to WT (WT LogEC50 -7.3 ± 0.08; LRRC8A KO LogEC50 -7.7 ± 0.12; * p <0.05, n=5). Relaxation to SNP or BAY60-2770 showed no difference between WT and KO. The LRRC8A-targeted VRAC inhibitor, montelukast (10 μM) reduced PE (10 -6 M)-induced contractile responses in the IPA (56 % decrease). Conclusions: These data demonstrate that LRRC8A plays an important role in controlling vascular reactivity that may be associated with ED. We speculate that LRRC8 channels are novel pharmacologic targets. Inhibition of the channels may reduce oxidative stress and improve sexual function. Disclosure: Work supported by industry: no.